ANALISIS GRAMATIKA ALIH KODE DARI BAHASA INGGRIS KE BAHASA INDONESIA ATAU SEBALIKNYA - -, Margana (Diksi, 2015)
In Indonesia, switching from one language to another language is a common phenomenon because Indonesian speakers are bilinguals. They use two or more languages, for example, Indonesian, English, or/and their own local language in a series of communication practices. With regard to the study of codeswitching, three perspectives can be used. They include pragmatic, sociolinguistic, and linguistic analyses. Of the three perspectives, analyzing codeswitching from a linguistic perspective seems to be interesting and challenging as the analysis gives an emphasis on the internal structure of the codeswitching itself. This article deals with code switching from English to Indonesian or vice-versa analyzed from grammatical aspects as part of the linguistic analysis. It aims at reviewing the grammatical rules underlying the code-swictching. Keywords: code-switching, grammatical analysis